Omental adipocytes enhance the invasiveness of gastric cancer cells by oleic acid-induced activation of the PI3K-Akt signaling pathway. (March 2017) - Xiang, Fan; Wu, Ke; Liu, Yulin; Shi, Liang; Wang, Di; Li, Gang; Tao, Kaixiong; Wang, Guobin
Abstract: A considerable number of patients with advanced gastric cancer have a clear predilection for metastasis to the great omentum, an organ mainly composed of adipose tissue. However, it remains unclear why tumor cells preferentially spread to and progress in the omentum. Here, we used a two-dimensional co-culture system to simulate the crosstalk between adipocytes and gastric cancer cells and showed that after co-culture with isolated omental adipocytes, gastric cancer cells exhibited a significant increase in lipid uptake and enhanced invasiveness. A lipidomic study showed that gastric cancer cells accumulated higher levels of oleic acid during the co-culture. By performing an assay of key enzymes in lipid synthesis, we demonstrated that the increased amount of oleic acid in gastric cancer cells mainly came from the adjacent adipocytes in the co-culture system. Furthermore, our data showed that at a certain concentration range, oleic acid treatment enhanced the invasiveness of gastric cancer cells in vitro and in a CAM assay, through the PI3K/Akt pathway, with the associated increased expression of the key pro-invasion factor MMP-2. Taken together, our results demonstrated that adipocytes may serve as an exogenous source of oleic acid that promotes gastric cancer cell invasion through the PI3K/Akt signaling pathway.